High Prevalence and Factors Associated With the Distribution of the Integron intI1 and intI2 Genes in Scottish Cattle Herds - Fernández Rivas, Cristina; Porphyre, Thibaud; Chase-Topping, Margo E.; Knapp, Charles W.; Williamson, Helen; Barraud, Olivier; Tongue, Sue C.; Silva, Nuno; Currie, Carol; Elsby, Derek T.; Hoyle, Deborah V. (Frontiers in Veterinary Science, 2021)
Integrons are genetic elements that capture and express antimicrobial resistance genes within arrays, facilitating horizontal spread of multiple drug resistance in a range of bacterial species. The aim of this study was to estimate prevalence for class 1, 2 and 3 integrons in Scottish cattle and examine whether spatial, seasonal or herd management factors influenced integron herd status. We used faecal samples collected from 108 Scottish cattle herds in a national, cross-sectional survey between 2014-2015, and screened faecal DNA extracts by multiplex PCR for the integrase genes intI1, intI2 and intI3. Herd-level prevalence was estimated (95% confidence interval (CI)) for intI1 as 76.9% (67.8 – 84.0%) and intI2 as 82.4% (73.9 – 88.6%). We did not detect intI3 in any of the herd samples tested. A regional effect was observed for intI1, highest in the North East (OR 11.5, 95% CI: 1.0 – 130.9, P = 0.05) and South East (OR 8.7, 95% CI: 1.1 – 20.9, P = 0.04), lowest in the Highlands. A generalized linear mixed model was used to test for potential associations between herd status and cattle management, soil type and livestock density variables. Within the final multivariable model, factors associated with herd positivity for intI1 included spring season of the year (OR 6.3, 95% CI: 1.1 – 36.4, P = 0.04) and watering cattle from a natural spring source (OR 4.4, 95% CI: 1.3 - 14.8, P = 0.017), and cattle being housed at the time of sampling for intI2 (OR 75.0, 95% CI: 10.4 – 540.5, P < 0.001). This study provides baseline estimates for integron prevalence in Scottish cattle and identifies factors that may be associated with carriage that warrant future investigation.